Letrozole vs estradiol valerate induced PCOS in rats: glycemic, oxidative and inflammatory status assessment. Issue 4 (April 2016) - Dăneasă, Alexandra; Cucolaş, Cristina; Lenghel, Lavinia Manuela; Olteanu, Diana; Orăsan, Remus; Filip, Gabriela A
Abstract : The objective of our study was to investigate glycemic, oxidative/antioxidative and inflammatory status in letrozole and estradiol valerate induced polycystic ovarian syndrome (PCOS) models. Sixty adult female Wistar rats were divided into four groups: L (0.2 mg letrozole/0.5 ml carboxymethyl cellulose (CMC), daily for 30 days), the control group CL, EV (one i.m. injection of 5 mg EV/0.5 ml sesame oil) and its corresponding control group CEV . After 30 days, ovarian morphology was assessed through ultrasound, serum free testosterone was determined, and an oral glucose tolerance test was performed. Blood, muscle, liver and periovarian adipose tissue (POAT) were collected for oxidative/antioxidative and inflammatory status evaluation. Free testosterone was increased only in the L group, while fasting glycemia was higher in the EV group. Both L and EV led to a significantly decreased level of muscle malondialehyde (MDA) and liver glutathione peroxidase (GPx) activity, while in POAT, MDA level diminished and GPx activity increased. The only difference between the two protocols was in muscle, where after L administration, GPx activity was significantly lower. Implementation of both protocols resulted in an increased expression of pNFKB in muscle, liver and POAT. The expression of monocyte chemoattractant protein 1 (MCP1) increased in liver and POAT after L administration, while in the EV group, MCP1 and STAT3 decreased in POAT. Our study shows that both protocols are characterized by an inflammatory environment in the usually insulin resistant tissues of human PCOS, without generating oxidative stress. In addition, EV has mild metabolic effects and unexpected interference with MCP1 expression in POAT, which require further investigation.